Divergência genética e seleção de variedades locais e cultivares de feijão com base em descritores morfológicos, agronômicos, tecnológicos e minerais - Santos, Guilherme Godoy dos (2020)
The local varieties of beans from family farming are an important genetic resource, whereas the cultivars improved by the breeding programs have characteristics that meet the interests of farmers and the consumer market. The objective of this research was to characterize the germplasm evaluated using morphological, agronomic, technological and mineral descriptors; study the correlations between these characters; analyze the genetic dissimilarity of local varieties and bean cultivars for these traits; and select superior genotypes for the different characters. For that, 49 bean genotypes were evaluated, 37 local varieties and 12 bean cultivars developed by the research. The 48 morphological descriptors provided by the Ministry of Agriculture, Livestock and Supply (MAPA) were evaluated in the 2018/19 harvest. Agronomic, technological and mineral traits were analyzed in three experiments conducted in the second crop (2017 and 2018) and the first crop (2017/18). The use of morphological descriptors is efficient to distinguish all the evaluated genotypes, there is genetic variability for practically all the evaluated characters. The indirect selection for grain yield can be performed based on the height of insertion of the last pod and the number of pods per plant, in addition there is a positive and high magnitude correlation between mass of 100 grains and length of grains. Tocher's method made it possible to identify promising parents for breeding programs aimed at plants of greater cycle, erect architecture and high grain yield. The selection indexes identify the genotypes for agronomic traits: Fepagro Triunfo, IPR Juriti, Guapo Brilhante, BRS Campeiro and Vagem Roxa; and the following genotypes for technological and mineral characters, of clear coat: Preguiçoso, Inhoque, Carioca (Vila Nova do Sul), Trindade and Pérola; and dark tegument: Argentino, Turrialba, Banana, Vagem Roxa and Paraná.